2001
DOI: 10.1667/0033-7587(2001)155[0156:vdrirt]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Resistance inRAS-Transformed Keratinocytes: Mechanism and Reversal Strategies

Abstract: Human retinoid X receptor alpha (hRXRalpha) plays a critical role in DNA binding and transcriptional activity through its heterodimeric association with several members of the nuclear receptor superfamily, including the vitamin D receptor (VDR). Several cancer cell lines derived from different tissues have been shown to be resistant to the growth-inhibitory action of 1,25-dihydroxyvitamin D(3) [1,25(OH)(2)D(3)], the biologically active metabolite of vitamin D(3). Here we show that in RAS-transformed keratinocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…It is possible that ERK facilitates the early, proliferative phase of differentiation [9,11,12,117], thus increasing the numbers of differentiated cells, rather than being related to the expression of the differentiated phenotype. This is consistent with the observation that the MEK/ERK inhibitor PD98059 substantially reduces, but does not totally prevent, 1,25(OH) 2 D 3 -induced differentiation (e.g., [13]), and the report that transformation of immortalized keratinocytes with Ha-Ras oncogene, an upstream regulator of the MEK/ERK pathway, results in resistance to the anti-proliferative action of 1,25(OH) 2 D 3 [118].…”
Section: Map Kinase Pathwayssupporting
confidence: 91%
“…It is possible that ERK facilitates the early, proliferative phase of differentiation [9,11,12,117], thus increasing the numbers of differentiated cells, rather than being related to the expression of the differentiated phenotype. This is consistent with the observation that the MEK/ERK inhibitor PD98059 substantially reduces, but does not totally prevent, 1,25(OH) 2 D 3 -induced differentiation (e.g., [13]), and the report that transformation of immortalized keratinocytes with Ha-Ras oncogene, an upstream regulator of the MEK/ERK pathway, results in resistance to the anti-proliferative action of 1,25(OH) 2 D 3 [118].…”
Section: Map Kinase Pathwayssupporting
confidence: 91%
“…The other potential MAPK consensus sequence located around threonine 82 (9) was not phosphorylated indicating that serine 260 was likely the major site of phosphorylation of the Ras-Raf-MAPK cascade in this model. Our studies also indicated that the Ras-Raf MAPK cascade also affected the response to LG1069, a specific RXR␣ ligand (9,20), raising the possibility that serine 260 phosphorylation of RXR␣ could also affect other partners of the RXR␣ such as RXR␣⅐RXR␣, RXR␣/RAR␣, RXR␣/ TR␤, and RXR␣/PPAR␥. Indeed, subsequent studies by MatsushimaNishiwaki et al (10) indicated that vitamin A signaling through RAR␣⅐ RXR␣ was also impaired by MAPKdependent phosphorylation at serine 260 in hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 60%
“…In addition, phosphoserine 260 RXR␣ has been reported to interfere with vitamin D3 receptor/ RXR-dependent signaling, and thereby confers a hormone-resistant growth advantage in ras-transformed human keratinocytes. 34,35 Thus, phosphorylation of RXR␣ might well be linked to the carcinogenic process by impairing its function as well as by accumulating its inactive or nontransactivating receptor, resulting in the failure to regulate cell proliferation.…”
Section: Discussionmentioning
confidence: 99%